2020
DOI: 10.1039/c9cc08335a
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective SNAr reaction of the phenoxathiin-based thiacalixarene as a route to a novel macrocyclic skeleton

Abstract: The formation of a novel type of macrocyclic skeleton possessing meta- and para-bridging units can be achieved by SNAr cleavage of an easily accessible phenoxathiin-based thiacalix[4]arene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…MeO − ) cleaves the phenoxathiin system, forming macrocycle 6 that possesses features of both pillararenes (para-bridge) and calixarenes (meta-bridge). 14 Interestingly, the reaction with S-nucleophile (NaSH) yields the unexpected linear tetramer bis-sulnic acid 7 with a rearranged phenoxathiin moiety. 15 The complex reaction pathway proceeds via a unique cascade of three consecutive S N Ar steps triggered by the initial attack of the SH − nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…MeO − ) cleaves the phenoxathiin system, forming macrocycle 6 that possesses features of both pillararenes (para-bridge) and calixarenes (meta-bridge). 14 Interestingly, the reaction with S-nucleophile (NaSH) yields the unexpected linear tetramer bis-sulnic acid 7 with a rearranged phenoxathiin moiety. 15 The complex reaction pathway proceeds via a unique cascade of three consecutive S N Ar steps triggered by the initial attack of the SH − nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…10 Similarly, it was found that compound 5 can be used for further unexpected reactions. In the presence of alkoxides, it is subject to a nucleophilic attack 11 leading to a hitherto unexplored type of macrocycle 6 , or it undergoes an unprecedented cascade of nucleophilic cleavage/rearrangements (with SH − ) to form linear oligomers 7 (Scheme 1). 12…”
Section: Introductionmentioning
confidence: 99%
“…10 Similarly, it was found that compound 5 can be used for further unexpected reactions. In the presence of alkoxides, it is subject to a nucleophilic attack 11 leading to a hitherto unexplored type of macrocycle 6, or it undergoes an unprecedented cascade of nucleophilic cleavage/ rearrangements (with SH − ) to form linear oligomers 7 (Scheme 1). 12 In this paper, we focused on some other interesting aspects of oxidised compound 5 and related systems concerning their unusual stereochemical preferences during the oxidation of sulfur bridges.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, while transition metal–catalyzed arylation reactions have been utilized previously to synthesize conjugated and/or heteroatom-linked polyaromatic macromolecules ( Figure 1 ), ( Zhang et al, 1992 ; Louie and Hartwig, 1998 ; Sadighi et al, 1998 ; Liess et al, 2006 ), there are (to the best of our knowledge) currently no transition metal-free reactions available to achieve exponential polymer growth for conjugated or heteroatom-linked polyaromatic structures. We are now able to meet this synthetic challenge by marrying iterative exponential polymer growth with nucleophilic aromatic substitution (S N Ar) reactions ( Beugelmans et al, 1994 ; Blaziak et al, 2016 ; Landovsky et al, 2019 ) with a unique masking/unmasking technique. Unmasking was achieved by simply oxidizing aromatic sulfides to sulfones—a mild, simple, and scalable reaction well suited for IEG applications.…”
Section: Introductionmentioning
confidence: 99%